Analisis Faktor-Faktor Penyebab Kepailitan Sritex - Mutia Karunia Antap Wulan; Sayuti Chow; Susan Ratna Salim; Ovalia Rukmana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The bankruptcy of PT Sri Rejeki Isman Tbk (Sritex), once one of Indonesia’s largest and most prominent textile manufacturers, represents a significant case of strategic failure within an increasingly competitive global manufacturing environment. Despite its long-standing reputation as a major exporter and supplier to international fashion brands and military institutions, Sritex ultimately collapsed under mounting financial and strategic pressures. This study aims to identify and explain the key internal and external factors that led to Sritex’s bankruptcy, while drawing strategic lessons for firms operating in export-oriented manufacturing industries. The research adopts a qualitative case study approach using secondary data collected from academic publications, industry reports, corporate documents, and credible news sources from 2023-2024. Data were analyzed through an integrated strategic management framework comprising SWOT analysis, Porter’s Five Forces, and the VRIO model to assess competitive pressures, strategic positioning, and resource sustainability. The findings indicate that Sritex’s former competitive strengths were no longer sufficient to withstand structural changes in the textile industry. Intense global competition, rising imports, and shifting demand patterns were compounded by internal weaknesses, including excessive leverage, rigid operations, and inadequate risk management. These factors collectively accelerated the firm’s financial distress and organizational breakdown. The study highlights the importance of strategic adaptability, prudent financial governance, and alignment between internal capabilities and external industry dynamics.